Pemanfaatan Limbah Bambu Sebagai Motivasi Mahasiswa Berwirausaha: - - Yusro Hakimah (Forum Kerjasama Pendidikan Tinggi, 2023)
Increasing waste in the community motivates students to be creative in increasing income. This service aims to provide insight and knowledge to students in utilizing bamboo waste around their homes into high-value items, doing creativity on the bamboo waste by making miniature ship crafts. The implementation method is carried out in three ways, namely, planning, implementation and evaluation. Planning is done by looking for ideas for making types of ships, followed by looking for references on how to make ships on YouTube. The implementation is done by preparing tools and materials, then making ships while viewing tutorials on YouTube. The evaluation was carried out by presenting the results of the miniature ship to lecturers and students of class RP4A of the Management study program of Tridinanti University. From the results of the presentation, many are interested in ordering ships and students have felt the benefits of waste.